THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND MENSTRUAL CYCLE WITH THE INCIDENCE OF DYSMENORHEA IN ADOLESCENT GIRLS IN SOLOK VILLAGE, RUMBIO JAYA DISTRICT IN 2026 - Miftahurrahmi; Fitri Handayani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Dysmenorrhea is one of the most common complaints experienced during menstruation by women, especially teenagers. This complaint usually occurs in the lower abdomen. Dysmenorrhea occurs because the uterine wall contracts when the hormone prostaglandin increases. The process of shedding the uterine wall is assisted by this hormone, which ultimately causes pain. This problem affects at least 60-85% of adolescent girls, resulting in high school absences. The purpose of this study was to determine the relationship between nutritional status and menstrual cycles with the incidence of dysmenorrhea in adolescent girls in Solok Village, Rumbio Jaya District. The method used in this study was a quantitative method with a cross-sectional approach. The population in this study were all adolescent girls in Solok Village, Rumbio Jaya District. So, a sample of 60 people was taken using a total sampling technique. Data collection was carried out using a questionnaire. The collected data were then processed and analyzed using the SPSS version 20 statistical program and analyzed using chi-square. The results of the study showed that there was a relationship between nutritional status and the incidence of dysmenorrhea in adolescent girls in Solok Village, Rumbio Jaya District, with the chi square test results showing a p-value of 0.000 p<0.05. There was a relationship between the menstrual cycle and the incidence of dysmenorrhea in adolescent girls in Solok Village, Rumbio Jaya District, with the chi square test results showing a p-value of 0.000 p<0.05.